1998
DOI: 10.2337/diacare.21.6.943
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Treatment of Cystic Fibrosis-Related Diabetes: A survey of current medical practice in the U.S

Abstract: Screening for IGT is not routinely done in CF patients and screening tests vary. Greater agreement exists on methods of treating patients with persistent IGT or CFRD, although goals and aggressiveness of treatment vary with the provider's background. A consensus conference is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 4 publications
(4 reference statements)
2
25
0
1
Order By: Relevance
“…In our study, both CFRD and CF-ITG patients scored significantly lower than CF-NGT patients with respect to all clinical parameters evaluated. Whereas onset of CFRD is associated with deterioration of pulmonary function and weight loss (complications that can reverse under insulin therapy (14,20)), reports on the possible impact of IGT in clinical deterioration of CF patients are scarce in the literature (38,39). In this study, we found that the severity of impairment of glucose metabolism is inversely correlated with all indices for CF clinical status.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…In our study, both CFRD and CF-ITG patients scored significantly lower than CF-NGT patients with respect to all clinical parameters evaluated. Whereas onset of CFRD is associated with deterioration of pulmonary function and weight loss (complications that can reverse under insulin therapy (14,20)), reports on the possible impact of IGT in clinical deterioration of CF patients are scarce in the literature (38,39). In this study, we found that the severity of impairment of glucose metabolism is inversely correlated with all indices for CF clinical status.…”
Section: Discussionsupporting
confidence: 61%
“…The well-established benefit of insulin replacement on reversion of clinical deterioration in CF patients (38,40) is currently not well documented for the pre-diabetic state. Recent studies have demonstrated that early insulin therapy improves anabolism and clinical status in CF patients with IGT, providing good glycemic control with few episodes of severe hypoglycemia (38,41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 In Canada, similar improvements have been reported, with (rounded) median survival being 24 years in 1982, and 29, 34, 33 and 37 years in 1987, 1992, 1997 and 2002, respectively, reaching 48 years in 2007. 27 The severity of CF can be assessed by the Shwachman clinical score (SS), which allocates points for general activity, physical examination, nutritional status and radiographic findings with a score out of 100, with severe disease having a score of < 40.…”
Section: Pathologysupporting
confidence: 56%
“…A survey in the USA by Allen et al 80 found a wide range of screening practices and tests, with random PG the most common, followed by HbA 1c , and urinary glucose. 80 Very few used the OGTT.…”
Section: Decision Analysismentioning
confidence: 99%